The Role of Virtual and Augmented Reality in Employee Training and Development. - Sreeram Daida, J. Lavanya, Gita Desai (Journal of Informatics Education and Research, 2025)
Virtual Reality (VR) and Augmented Reality (AR) are revolutionizing employee training and development by offering immersive, interactive, and cost-effective learning experiences. These technologies enable organizations to enhance skill acquisition, improve knowledge retention, and create safe environments for hands-on practice. This paper explores the role of VR and AR in workforce training, highlighting their benefits, challenges, and future implications. VR provides a fully immersive environment where employees can engage in real-world simulations without the risks associated with traditional training. It is particularly useful in high-stakes industries such as healthcare, manufacturing, and aviation, where hands-on experience is crucial. Meanwhile, AR overlays digital information onto the physical world, offering real-time guidance and enhancing on-the-job training for sectors like retail, logistics, and technical maintenance. The adoption of VR and AR in training programs has been shown to enhance engagement and motivation, leading to improved learning outcomes compared to conventional methods. These technologies also support remote training, reducing logistical constraints and ensuring a standardized learning experience across global organizations. However, challenges such as high implementation costs, technical limitations, and user adaptation must be addressed to maximize their potential.